An Analytical and Experimental Study of the Linear Fresnel Reflector Solar Concentrator System - Manikumar, R.; Arasu, Dr. A. Valan (Distributed Generation & Alternative Energy Journal, 2014)
A solar hot water generation system that makes use of a linear Fresnel reflector solar concentrator (LFRSC) technique to concentrate solar radiation onto a stationary absorber cavity suspended above the concentrator plane is proposed. Heat loss from the trapezoidal cavity absorber occurs via a complex interaction between radiation, convection and conduction within the cavity, and then from cavity to the surroundings. This article describes and compares experimental and analytical methods used to investigate the heat losses from the cavity absorbers with and without plate underneath the absorber tubes. Reasonable agreement is achieved between the two methods for heat loss in the cavity absorber. Also, analytical and experimental thermal performance analysis of LFRSC system is determined. The results are presented and discussed.